GENDER, CHANGE, AND EDUCATION : CASE STUDY: NON-FORMAL EDUCATION PERSPECTIVE IN PEPI Al-BAYQUNIE’S BOOK "CALABAI PEREMPUAN DALAM TUBUH LELAKI" - Muh Aidil Putra (Marwah: Jurnal Perempuan, Agama dan Jender, 2023)
The historical aspect of the story contributes to the unhealed trauma and strong stereotypes in traditional society about the position of men and the demands placed on them. Puang Matoa Saidi, later called Calabai (in Bugis), is a man with the character of a woman. He was born into a different situation, and grew up under the harsh upbringing of his father (Puang Baso), who considered Saidi's physical condition a disgrace to the family. However, the female character in Saidi's male physique, rejects all treatment from Puang Baso (Saidi's father), that the activities of hoeing, gardening, lifting heavy things, being the head of the family are symbols that should be pinned to a man. By using the Content Analysis Approach-descriptive method. It leads us to understand that there are several main factors that build gender labeling itself, including the development of globalization which focuses on the argument that, labeling of men in the era of globalization has shifted meaning due to technological advances and behavioral changes. Differences in geographical conditions make people's choices very much determined by the conditions in which they live and patriarchal culture contributes more or less to the debate about the position of women before men. And the presence of religious normative interference looks more at aspects of behavior that are based on whether it is prohibited or not.